Strategi Manajemen Pengetahuan untuk Mengoptimalkan Operasi Help Desk: Tinjauan Literatur Sistematis - Lathiful Alamsyah; Fachri Munandar; Dana Indra Sensuse; Sofian Lusa; Nadya Safitri; Damayanti Elisabeth (AI Society & STMIK Indonesia, 2025)
In today's digital era, effective knowledge management (KM) is vital for businesses, especially in public sector help desks where user interaction is critical. This systematic literature review (SLR) explores factors influencing KM implementation and identifies strategies to optimize help desk operations. Using PRISMA criteria and the PICO model, 25 studies from 2019 to 2024 were selected after screening 5,490 publications. Key factors impacting KM include organizational culture, leadership support, and technological infrastructure. Recommended strategies involve fostering a knowledge-sharing culture, developing knowledge bases, and utilizing AI for knowledge capture. The findings contribute theoretically by consolidating a framework for KM in help desks and practically by guiding public sector organizations. However, reliance on secondary data limits the study, as it may not fully reflect real-world KM practices. Future research could empirically validate these findings and explore emerging technologies like AI to enhance KM effectiveness.